Atypical Teratoid/Rhabdoid Tumors in Adult Patients: CT and MR Imaging Features - Han, L.; Qiu, Y.; Xie, C.; Zhang, J.; Lv, X.; Xiong, W.; Wang, W.; Zhang, X.; Wu, P. (American Journal of Neuroradiology, 2011)
SUMMARY: Primary AT/RT is a rare highly malignant tumor of the CNS, usually occurring in children younger than 5 years of age. The objective of this study was to characterize the CT and MR imaging findings in a series of 5 adult patients with pathologically proved AT/RT. All 5 AT/RTs were supratentorial. In 2 patients who underwent nonenhanced CT, the tumors appeared isoattenuated, and 1 of the 2 tumors contained calcifications. Solid portions of the tumors on MR imaging were isointense on T1-weighted, T2-weighted, and FLAIR images, and 1 case showed restricted diffusion on DWI. The tumors also demonstrated a bandlike rim of strong enhancement surrounding a central cystic area on contrast-enhanced T1-weighted imaging. One tumor was associated with destruction of the calvaria. Although AT/RTs can have nonspecific findings, the tumors in our series were large and isointense on T1-weighted, T2-weighted, and FLAIR images with central necrosis and prominent rim enhancement. ADCapparent diffusion coefficientAT/RTatypical teratoid/rhabdoid tumorCNScentral nervous systemDWIdiffusion-weighted imagingFLAIRfluid-attenuated inversion recoveryLleftmRNAmessenger ribonucleic acidN/Anot availableNDnot depictedOSoverall survivalPNETprimitive neuroectodermal tumorPRpartial resectionRrightTRtotal resection